PEMBERIAN EDUKASI TENTANG CARA MENGATUR OBAT BAGI LANSIA AGAR TETAP SEHAT SELAMA RAMADHAN DI UPT PSTW HUSNUL KHOTIMAH - Djohari, Meiriza; Pratiwi, Erniza; Fadhli, Haiyul; Safitri, Devi; Rifani, Mhd; Putri, Sella Hilmalia Nur Al; Sumbarita, Silvia; Rahmatunnur, Siti; Mardianti, Tengku Shella; Muti’ah, Try Hadirah; Azizah, Wahyu; Zamri, Wiedya Alfitrya; Maqfiroh, Wirdarani (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
Elderly people who undergo regular drug therapy often face problems in adjusting the time they take medication during fasting. This is due to changes in eating schedules during Ramadan. Some medications may require adjustments in dose, frequency, or even formulation so that they continue to work well. The aim of this service is to increase public understanding, especially the elderly, about how to manage medication schedules and doses during fasting. Service activities are carried out using a demonstration and discussion system by giving brochures to the elderly at UPT PSTW Husnul Khotimah. Starting from filling out the questionnaire sheet (pre-test), distribution of brochures, verbal education and ending with filling out a questionnaire sheet (post-test) related to participants' understanding of the information that has been presented. Based on the results, an increase in the average value was obtained pre-test by 41.25% to 72.16% in post-test, and in statistical tests with Paired Sample Test shows a significance value of 0.000, which indicates there is a significant difference between before and after counseling. So it can be concluded that the counseling carried out at UPT PSTW Husnul Khotimah significantly increased the knowledge of the elderly, especially regarding the use of medication during fasting.